El senderismo como actividad saludable, para mejorar la calidad de vida durante el tiempo libre de los niños, barrio San José de Vilcabamba cantón Loja - Granda Granda, Henry Victoriano (2016)
The current research is focused, to know HOW HEALTHY ACTIVITY HIKING TO IMPROVE THE QUALITY OF LIFE IN THE FREE TIME OF CHILDREN, BARRIO SAN JOSE, and Vilcabamba Loja Canton. This process of research projects the child to the care and benefit of their health through walking as a physical activity. The research is qualitative, longitudinal study pre-experimental design and specific objectives basing globally and diagnose, hiking and knowledge as a healthy activity during leisure time. Planning an alternative according to the resources and capacity of the child. Proposal and validate a test application and methodological programs and develop exercises to improve physical condition of children of Barrio San José. In research for the purpose of this thesis we have used some methods such as induction, deduction, -synthesis analysis, historical sense, empirical observation and survey methods, theoretical methods modeling, system approach, probabilistic, mathematical, scientific content analysis methods. Likewise it was found that children have a low interest in physical activity by the lack of knowledge on hiking as a healthy activity to improve the quality of life. Getting the author to the conclusion that there is failure in the physical condition and state of actual lives of children, lack of organization, planning and implementation of basic physical exercises, by the neighborhood leader and discouragement by parents Barrio San Jose.